Occurrence, Abundance and Distribution of Bleak, Common Spirlin, and Sunbleak in the Environmental Gradients of Small Rivers (Tatarstan) - Askeyev Arthur (Sciendo, 2021)
The probability of occurrence, distribution, and abundance of bleak, common spirlin, and sunbleak in 316 small rivers of the Republic of Tatarstan were studied. The studied region has a high geographical and environmental heterogeneity. The impact of environmental factors on species occurrence was analyzed with generalized linear models. Among the selected fish, sunbleak had the highest probability of occurrence, and bleak had the highest abundance. Elevation was the only environmental variable significantly affecting the probability of occurrence of all three species. With an increase in elevation, the probability of occurrence of bleak, common spirlin, and sunbleak significantly decreased. Optimum values and niche breadth differed significantly between fish species for some of the environmental variables.